Implementasi Data Mining dalam Mengklasifikasikan UKT (Uang Kuliah Tunggal) pada UIN Sumatera Utara Medan - Triase Triase; Samsudin Samsudin (Universitas Asahan, 2020)
Abstract – Single Tuition Fee (UKT) is a tuition payment system that is applied in Indonesian public tertiary institutions, especially for undergraduate programs starting from the 2013/2014 - present academic year. UKT payments that are borne by each student are not the same, due to the cross subsidy system based on the economic and social conditions of the student's parents / guardians. The State Islamic University of North Sumatra Medan (UINSU) is one of the state universities that applies the UKT payment system into 7 groups, namely Group I, Group II, Group III, Group IV, Group V, Group VI, Group VII. The results of the survey to students showed that some students received a UKT amount that was not in accordance with the UKT group, and UINSU gave students the opportunity to appeal to UKT. The appeal process caused the UKT committee to take time. Therefore, the researcher will provide a solution with the classification technique data mining, namely the Naïve Bayes Algorithm. The algorithm serves to predict the suitability of the UKT size group for new students. The results can be used to design a decision support system in classifying the UKT amount for new students so that it can be used as a recommendation for the university in determining the new student UKT group.Keywords - UKT, Data mining, Classification, Naïve bayes. Abstrak – Uang Kuliah tunggal (UKT) merupakan sistem pembayaran uang kuliah yang diterapkan di perguruan tinggi negeri Indonesia khususnya untuk program sarjana dimulai dari tahun akademik 2013/2014 sampai saat ini. Pembayaran UKT yang ditanggung oleh setiap mahasiswa tidak sama, dikarenakan adanya sistem subsidi silang yang didasarkan atas kondisi ekonomi dan sosial orang tua/wali mahasiswa. Universitas Islam Negeri Sumatera Utara Medan (UINSU) adalah salah satu perguruan tinggi negeri yang menerapkan sistem pembayaran UKT menjadi 7 kelompok yaitu Kelompok I, Kelompok II, Kelompok III, Kelompok IV, Kelompok V, Kelompok VI, Kelompok VII. Hasil survey kepada mahasiswa, bahwa beberapa mahasiswa mendapat besaran UKT tidak sesuai dengan kelompok UKT, dan UINSU memberikan kesempatan kepada mahasiswa untuk banding UKT. Proses banding menyebabkan memakan waktu panitia UKT. Oleh sebab itu, peneliti akan memberikan solusi dengan datamining teknik klasifikasi yaitu Algoritma Naïve bayes. Algoritma berfungsi untuk memprediksi kesesuaian kelompok besaran UKT mahasiswa baru hasilnya dapat digunakan untuk merancang sistem pendukung keputusan dalam mengklasifikasikan besaran UKT mahasiswa baru sehingga dapat dijadikan rekomendasi bagi pihak universitas dalam menentukan kelompok UKT mahasiswa baru.Kata kunci – UKT, Data mining, Klasifikasi, Naïve bayes.